Assessment of Gastrointestinal Toxicity in Head and Neck Cancer (HNCS) Patients Receiving Platinum Compounds Chemotherapy at a Tertiary Care Hospital - Panchawat, Pooja; Dhakar, Manish; Parihar, Narendra Bheemraj; Mishra, Renu; Rathore, Mahendra Singh (Indian Journal of Pharmacy Practice)
Background: Platinum-based chemotherapy, including cisplatin and carboplatin, is a standard treatment for head and neck cancers. However, Gastrointestinal (GI) toxicity remains a common adverse effect that may affect treatment tolerability. Comparative real-world data on GI toxicity patterns between cisplatin and carboplatin are limited. Materials and Methods: A prospective observational study was conducted over six months at a tertiary care hospital, enrolling 140 patients with head and neck cancer receiving platinum-based chemotherapy. Gastrointestinal adverse events were monitored during each chemotherapy cycle and graded using the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Toxicity patterns were analyzed according to demographic characteristics, residential status, treatment cycles, chemotherapy regimens, and type of platinum compound. Results: Out of 140 patients, 123 experienced gastrointestinal toxicity, with a total of 133 toxicity events recorded. Grade 1 toxicity was most common, followed by Grade 2, while Grade 3 events were infrequent. Higher GI toxicity rates were observed among male patients, those aged 41-50 years, and rural residents. Toxicity incidence was greatest during early chemotherapy cycles (cycles 1-3). Cisplatin was predominantly associated with low-grade (Grade 1-2) GI toxicity, whereas carboplatin showed a relatively higher proportion of Grade 3 toxicity. Conclusion: Gastrointestinal toxicity was frequent in head and neck cancer patients receiving platinum-based chemotherapy and was influenced by both patient-related and treatment-related factors. Early identification of high-risk groups may facilitate timely supportive care and improve treatment tolerability.
Keywords: Gastrointestinal toxicity; Head and neck cancer; Platinum-based chemotherapy; Cisplatin; Carboplatin; CTCAE Scale